Environmental Economic Factors Affecting Banking Sector of IRAN: An Empirical Assessment Using the VEC Model - Sargolzaee, Mostafa; Rahbar, Farhad; Khalighi, Faramarz; Ahmadi, Razieh (IJRDO - Journal of Business Management, 2016)
This working paper has aimed to investigate the impacts of environmental economic factors affect the volume of banking deposit and loan with yearly data (1978-2013). We employed Vector Error Correction (VEC) model to estimate short-run and long-run relations. Detection of cointegration between variables was tested by Johansen cointegration test which indicates the deviation from longrun equilibrium. The empirical findings of this study show that total private and public consumption has adverse impact on volume of deposit and loan but GDP affects positively on them in the long-run. Moreover, the error correction part which represents the short run relations reveals that if the value of GDP lies above its long run equilibrium, then the volume of deposit and loan will increase nextperiod. As well as, we forecast the volume of these two variables for 201 4 and 2015.So it demonstrates that the volume of loan will grow about 24% for 2016 while loan growth rate will be 30%. According to our findings, we can suggest to policy makers that expansionary policies cause banking sector to be stable.